Cannabis use, subsequent other illicit drug use and drug use disorders: A 16-year follow-up study among Swedish adults. (July 2020) - Rabiee, Rynaz; Lundin, Andreas; Agardh, Emilie; Forsell, Yvonne; Allebeck, Peter; Danielsson, Anna-Karin
Highlights: This is a longitudinal cohort study comprising 10 345 Swedish men and women. It examines associations between cannabis use and other illicit drug use. Also, it examines associations between cannabis and drug use disorders. Cannabis users had an increased risk of other drug use at 3-year-follow-up. No independent association between cannabis use and drug use disorders was found. Abstract: Aims: To examine the association between cannabis use and subsequent other illicit drug use and drug use disorders (harmful use and dependence). Design, Setting, Participants: We used survey data from a population-based cohort in Stockholm County (collected 1998–2000), with linkage to the National Patient Register. The study base comprised participants aged 20–64 years (N = 10 345), followed-up until 2014. Cox and logistic regression analyses were conducted to test associations between self-reported cannabis use and risk of subsequent other illicit drug use (three-year follow-up) and drug use disorders (16-year follow-up). Findings: The odds ratio (OR) for other illicit drug use onset at three-year follow-up for lifetime cannabis users was 7.00 (4.47–10.35, 95% CI) and for recent cannabis users 34.41 (19.14–61.88, 95% CI). Adjusting for age and AUDIT score attenuated the association, for lifetime users: OR = 5.48 (3.69–8.13, 95% CI) and OR = 5.65 (3.80–8.41, 95% CI), and for recent users: OR = 18.32 (9.88–33.99, 95% CI) and OR = 20.88 (11.19–38.95, 95% CI). For cannabis users only, the hazard ratio (HR) for drug use disorders at 16-year follow-up was 0.89 (0.31–2.61, 95%CI). For cannabis and other illicit drug users, the corresponding HR was 7.27 (3.85–13.75, 95% CI). Conclusions: There was no independent association between cannabis use and subsequent drug use disorders. The association with subsequent drug use disorders was rather explained by other illicit drug use, which cannabis users were at higher risk of at the three-year follow-up.